The Role of Mediation in a Teacher’s Work - Ścieranka, Sandra (Journal of Education, Technology and Computer Science, 2022)
This article deals with the use of mediation in the educational space of the teacher’s work. It discusses the essence of mediation and the contemporary transformations and difficulties that are taking place in school institutions, directly related to the person of the teacher. The quintessence of the considerations is the presentation of mediation in the context of challenges for the teacher, as an alternative method to improve dialogue and alleviate emerging conflicts and misunderstandings especially in teacher-student, teacher-parent, and student-student relations.